2014
DOI: 10.5507/bp.2013.085
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors in cancer therapy. A review

Abstract: a Background. Despite recent success toward discovery of more effective anticancer drugs, chemoresistance remains a major cause of treatment failure. There is emerging evidence that epigenetics plays a key role in the development of the resistance. Epigenetic regulators such as histone acetyltransferases (HATs) and histone deacetylases (HDACs) play an important role in gene expression. The latter are found to be commonly linked with many types of cancers and influence cancer development. Overall, histone acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 98 publications
(99 reference statements)
1
46
0
Order By: Relevance
“…A substantial amount of research now indicates a role for http://dx.doi.org/10.1016/j.leukres.2014.08.014 0145-2126/Published by Elsevier Ltd. deregulated epigenetic mechanisms in cancer, both in the development of tumors and their acquisition of chemoresistance [14][15][16][17]. As a result, chromatin-modifying enzymes such as histone methyltransferases and demethylases [14], histone acetyltransferases (HAT), and histone deacetylases (HDAC) [15][16][17] are promising therapeutic targets. Histone deacetylases catalyze the removal of negatively charged acetyl groups from lysine residues in the core histones, which results in a more compact and transcriptionally repressed chromatin structure.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial amount of research now indicates a role for http://dx.doi.org/10.1016/j.leukres.2014.08.014 0145-2126/Published by Elsevier Ltd. deregulated epigenetic mechanisms in cancer, both in the development of tumors and their acquisition of chemoresistance [14][15][16][17]. As a result, chromatin-modifying enzymes such as histone methyltransferases and demethylases [14], histone acetyltransferases (HAT), and histone deacetylases (HDAC) [15][16][17] are promising therapeutic targets. Histone deacetylases catalyze the removal of negatively charged acetyl groups from lysine residues in the core histones, which results in a more compact and transcriptionally repressed chromatin structure.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to hyperacetylation of the respective substrates, HDACs inhibition is also known to lead to increased histone acetylation and consequent chromatin remodeling (Li et al, 2013;Xu et al, 2007). Under TSA treatment, chromatin relaxation is known to increase the expression of CDKN1A (cyclin-dependent kinases inhibitor, or p21) gene (Blagosklonny et al, 2002;Hrabeta et al, 2014;Ocker and Schneider-Stock, 2007;Xu et al, 2007). As such, CDKN1A (p21) expression is frequently used as a marker of HDAC inhibition (Harrison and Dexter, 2013;Huang et al, 2012;Xu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, it was recently shown that interfering with HDAC6 is sufficient to prevent microtubule deacetylation (Gold et al, 2015). There is growing evidence that HDACs inhibition is strongly associated with decreased cell mobility, which is of particular interest in the oncology field (Hrabeta et al, 2014;Ocker and Schneider-Stock, 2007). Although there are several studies showing that METH and other psychostimulants affect the expression of HDACs (Cassel et al, 2006;Host et al, 2011;Martin et al, 2012;Omonijo et al, 2014), and in particular the expression of HDAC6 (Omonijo et al, 2014), the effect of METH in microtubules acetylation was not yet explored.…”
Section: Introduction Methamphetamine (Meth) Is a Powerful Psychostimmentioning
confidence: 99%
“…In cell-based studies, HDACIs have been shown to induce cell cycle arrest, cell differentiation, and apoptosis. Furthermore, HDACIs were reported to intensify the host immune response and decrease angiogenesis [20][21][22][23][24]. For these reasons, several HDACIs are currently at various stages of clinical trials, individually or in combination with radiotherapy and/or chemotherapy for cancer treatment in patients with hematological and solid malignancies [25].…”
Section: Introductionmentioning
confidence: 99%